Kelebihan Pembayaran di SPBU dalam Kajian Filsafat Hukum Islam - Helmi Yusnita; Busyro Busyro (NALAR FIQH: Jurnal Hukum Islam, 2023)
Fuel oil (BBM) for vehicles can be obtained at the Public Fuel Filling Station (SPBU) closest to the sale and purchase transaction, filling is done according to the buyer's wishes. Payments are made according to the nominal value shown on the gas station monitor screen, but it often happens that payments are made in excess of what is shown on the gas station monitor. This research aims to explain the philosophical study of Islamic law regarding excess payments at gas stations, which exceed the bills that are monitored at gas stations. This research uses library research with the main data coming from journals, books, and the internet. Data collection was carried out by reading and grouping according to the themes discussed, then analyzed using descriptive, inductive theory and presenting it in writing. The research results show that philosophically in Islamic law, excess payments at gas stations are at the hajiyah level. Because it is done to make transactions easier and less difficult at the gas station.